The figure of the consumer in modernity: A Simmelian analysis of marketing business strategies - Szlechter, Diego (Athenea Digital, 2007)
We analyze the links between two conceptions of "the consumer" in modernity: one in Georg Simmel's classic book “Philosophy of money", and the other implicit in the marketing strategies of modern companies. In modernity, the division of labour, and social differentiation, have produced a general sense of intellectualization, in which objective culture and cultural products have acquired their own life, independently of their creators, who are more and more anonymous. This process makes possible a detachment of the subject from things. Money or, in Simmel's terms, the monetary economy, unifies all products through an abstract value. These products are converted from ends in themselves into means to other ends. This provides for two divergent paths forward, which reflect the ambivalent character of modernity: on the one hand, the subject can develop a hyper- developed appreciation of the world, achieving independence from the immediate necessities of life and developing an aesthetic sensitivity towards objective culture. But, on the other hand, the proliferation of consumption, and its penetration into almost all facets of life, can undermine and alienate even the most intimate space that the subject might try to keep private.